Epidemiology Characteristics of COVID-19 Infection Amongst Primary Health Care Workers in Qatar: March-October 2020 - Mohamed Ghaith Al-Kuwari; Mariam Ali AbdulMalik; Asma Ali Al-Nuaimi; Jazeel Abdulmajeed; Hamad Eid Al-Romaihi; Sandy Semaan; Mujeeb Kandy (Frontiers Media S.A., 2021)
Background: COVID-19 transmission was significant among Healthcare workers worldwide. In March 2020, Qatar started reporting numbers of COVID-19 positive cases among workers in Primary Health Care Corporation (PHCC). The study estimates the burden of the aforementioned infections and examines the demographic characteristics associated with the recorded positivity rates.Method: A cross-sectional descriptive study was conducted among Primary healthcare workers between March 1st and October 31st, 2020. The study examined the positivity rate of the different types of Primary healthcare workers and, analyzed the demographic characteristics of the infected persons.Results: 1,048 (87.4%) of the infected Health Care Workers (HCWs) belonged to the age group below 45 years, and 488 (40.7%) HCWs were females. 450 (37.5%) were HCWs clinical staff working in one of the 27 PHCC Health Centers (HCs) Despite the increased patient footfall and risk environment, the COVID dedicated HCs had an attack rate of 10.1%, which is not significantly different from the average attack rate of 8.9% among staff located in other HCs (p = 0.26). Storekeepers, engineering & maintenance staff, housekeeping staff, support staff, and security staff (outsourced non-clinical positions) had the highest positivity rates, 100, 67.2, 47.1, 32.4, and 29.5% respectively.Conclusion: The elevated risk of infection among outsourced non-clinical healthcare workers can be explained by environmental factors such as living conditions. Furthermore, better containment within clinical healthcare workers can be attributed to strict safety training and compliance with preventative measures which is recommended to be implemented across all settings.